Effect of root dipping with biofertilizer and foliar application of zinc on growth, yield and soil enzymatic activity in summer rice (Oryza sativa L.): Biofertilizer root dipping and Zn foliar spray on summer rice - MAITY , SUCHITA; Mondal, Ramyajit; Goswami, Saumi (ORYZA-An International Journal of Rice, 2025)
Imbalanced fertilizer use, nutrient unavailability, and significant fertilizer losses are common issues in summer (Boro) rice cultivation. A field experiment was conducted in 2023 at the Instructional Farm, Seacom Skills University, Birbhum, West Bengal, to evaluate the effect of biofertilizer root dipping, chelated zinc foliar spray, and recommended chemical fertilizers on boro rice cultivar MTU 1010. The experiment, laid out in a randomized complete block design (RCBD) with three replications, comprised eight treatments: T1-Recommended Dose of Fertilizer (RDF i.e., N:P2O5:K2O @ 100:50:50 kg ha-1), T2 - RDF + PSB root dip (5 g L-1), T3 - RDF + Azotobacter (5 g L-1), T4 - RDF + Azotobacter + PSB (10 g L-1), T5 - T1 + chelated Zn @ 0.25% foliar spray (15 & 30 DAT), T6 - T2 + Zn spray, T7 - T3 + Zn spray, T8 - T4 + Zn spray. Treatment T8 recorded the best performance in terms of plant height, dry matter accumulation, tiller number per hill, and root parameters (length, volume, dry weight). It also showed significant improvement in yield attributes-panicle number m-², panicle length and weight, number of grains per panicle, test weight-resulting in the highest grain and straw yields. Additionally, T8 enhanced soil enzymatic activity and improved post-harvest soil nutrient status. Economic analysis revealed T8 offered the highest gross and net returns and benefit-cost ratio. Thus, integrating RDF with Azotobacter + PSB root dipping (10 g L-1) and chelated Zn foliar spray (0.25% at 15 and 30 DAT) proves most effective for boro rice cultivation in the red and lateritic soils of West Bengal.